Pemanfaatan Upaya Kesehatan Perorangan (UKP) oleh Peserta Jaminan Kesehatan Nasional di Wilayah Kerja Puskesmas Tarus - Desnel Natalia Lende; Rina Waty Sirait; Dominirsep O. Dodo (Media Kesehatan Masyarakat, 2021)
To overcoming gaps in the utilization of health services by the poor, the government implements of National Health Insurance (JKN) program which is managed by BPJS Kesehatan. The Public Health Center (Puskesmas) was formed to reach the wider community, from the existence of the puskesmas and JKN, it’s hoped that the government's goals to achieve community welfare can be achieved. However, the utilization of puskesmas by JKN participants is still low. The purpose of this study was to determine the factors related to the utilization of health services by JKN participants in the working area of ​​Puskesmas Tarus. This type of the research is a quantitative study using a cross sectional design. The sample consisted of 100 people using the accidental sampling technique. Data analysis was performed using univariate and bivariate analysis with the spearmen correlation test. The results showed that the factors related to the utilization of health services by JKN participants were attitude (r=0.940; ρ=0,000), perception of pain (r=0.270; ρ=0.007), family support (r=0.340; ρ=0.001), and assessment of health centers (r=0,265; ρ=0.008), while the unrelated factor was knowledge (r=0.063; ρ=0.536). BPJS Kesehatan and puskesmas are expected to cooperate in providing related to the use of JKN. Puskesmas are expected to improve facilities and infrastructure so that the utilization of health service at the puskesmas can be increased.